Mobile Communication Device in English Language Learning: Motives and Constraints - Suparjan Suparjan (Journal of ELT Research: The Academic Journal of Studies in English Language Teaching and Learning, 2020)
The objective of this study is to investigate students’ motives and constraints in employing mobile communication device as a media for English language learning. Semi-structure interviews were applied to collect the data. The findings indicate that the students have a positive perception toward the use of mobile communication device for English language learning as it can facilitate them to develop their English language skills. The students also find that learning English with mobile communication device is flexible and fun. Mobile communication device can ease them to apply appropriate learning strategies for developing their English language skills. Despite the benefits that students have by applying mobile communication devices for learning the language, they also uncover several constraints. Low internet connection and high cost for online activities are constraints that students discover to be crucial. Key words: motive, mobile communication device, facilitate, English language skills, benefit, constraint